Adjustment of First Year Students to Work: Case Study - Annisa Nur Fauziah (Universitas Negeri Surabaya, 2023)
The purpose of this study is to identify the process of adjustment for the participant, who is an early-semester student and works, as well as the elements that support and prevent adjustment. A case study methodology and a qualitative technique are both used in this work. Participant are made up of three students and their three significant others, who are chosen according to preset standards. Semi-structured interviews were used to gather data, which was then analyzed using thematic analysis approaches. Passing interviews with a significant other were conducted to ensure the validity of the findings in this study. The study's findings show that the participant can modify his dual role of learning and working depending on a number of different conditions. One of these factors is scheduling time for work, school, and fun. Next, learn from mistakes, take time to reflect when there are issues, try to think optimistically in any circumstance, and ask or seek support from parents who have a lot of influence for assistance.